Assessment of Office-Based Care of Sexually Transmitted Diseases and Vaginitis and Antibiotic Decision-Making by Obstetrician-Gynecologists. Issue 6 (1998) - McGregor, J. A.; Hager, W. D.; Gibbs, R. S.; Schmidt, L.; Schulkin, J.
Abstract : Objective: Survey office-based obstetric-gynecologic practitioners regarding their knowledge of infectious disease care and antibiotic use. Methods: A survey questionnaire of multiple-choice questions was mailed to Fellows of the American College of Obstetricians and Gynecologists about clinical entities for which recommendations have undergone recent changes or about which there was a lack of consensus in a prior similar survey (Gibbs RS, McGregor JA, Mead PB, et al.: Obstet Gynecol 83:631–636, 1994). Results: Respondents indicated that oral metronidazole was their most frequent choice to treat bacterial vaginosis. Ampicillin (57%) was used more often than penicillin (39%) for intrapartum group B streptococcus prophylaxis. Azithromycin was preferred (61%) over erythromycin-base (38%) for chlamydia treatment during pregnancy. There were several modes of practice that deviated from accepted care: 27% and 29% did not screen for chlamydia and gonorrhea, respectively, in pregnancy; 17% used cultures for Gardnerella vaginalis to diagnose bacterial vaginosis; 25% considered quinolones to be safe in pregnancy; 93% felt metronidazole should never be used in pregnancy; and the majority (66%) would send a patient treated successfully for pelvic cellulitis home with an oral antibiotic. Conclusion: Respondents' infectious disease knowledge and practices in obstetrics and gynecology is appropriate in treating sexually transmitted diseases, bacterial vaginosis, and group B streptococcus. Numerous deficiencies still exist in screening for sexually transmitted diseases in pregnancy and diagnosing bacterial vaginosis, as well as in the choice of antibiotics to use or avoid for certain infections.